Economic measures to reduce the impacts of Covid-19 (Research, Society and Development, 2022)
The beginning of the year 2020 is marked by the coronavirus pandemic. In addition to the effects on public health, the disease has also impacted the world economy. This article aims to show the Covid-19 pandemic in the Brazilian reality in which the ideology of profit and economy prevails over the important values of life. In capitalism, social inequality is striking and concerns the National Health Council (CNS) when facing Covid-19 in Brazil. and it is always the poorest who, in addition to losing rights, pay the bill. The Covid-19 pandemic, which causes the most serious health crisis in the world in this first quarter of the 21st century, has generated many and diverse debates. From an expert to a housewife, the subject is the most talked about. And each one, at his choice, makes the defense that is closest to his life history and personal relationships. It is also essential to emphasize that in this context in which drastic measures are needed to contain the circulation of people, an even greater burden of domestic work and care for children, the elderly and the sick falls on women, especially black women. The research was bibliographic, descriptive and quantitative on the topic at hand. It is concluded that the scenario can be reversed, if the government commits to deliver economic reforms and promotes relevant privatizations. This time, only a profound change in investors' expectations about business potential in Brazil and in the world would be able to offset the harmful economic effects of the coronavirus.